Research priorities for the COVID‐19 pandemic and beyond: A call to action for psychological science. (19th July 2020) - O'Connor, Daryl B.; Aggleton, John P.; Chakrabarti, Bhismadev; Cooper, Cary L.; Creswell, Cathy; Dunsmuir, Sandra; Fiske, Susan T.; Gathercole, Susan; Gough, Brendan; Ireland, Jane L.; Jones, Marc V.; Jowett, Adam; et al.
Abstract : The severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) that has caused the coronavirus disease 2019 (COVID‐19) pandemic represents the greatest international biopsychosocial emergency the world has faced for a century, and psychological science has an integral role to offer in helping societies recover. The aim of this paper is to set out the shorter‐ and longer‐term priorities for research in psychological science that will (a) frame the breadth and scope of potential contributions from across the discipline; (b) enable researchers to focus their resources on gaps in knowledge; and (c) help funders and policymakers make informed decisions about future research priorities in order to best meet the needs of societies as they emerge from the acute phase of the pandemic. The research priorities were informed by an expert panel convened by the British Psychological Society that reflects the breadth of the discipline; a wider advisory panel with international input; and a survey of 539 psychological scientists conducted early in May 2020. The most pressing need is to research the negative biopsychosocial impacts of the COVID‐19 pandemic to facilitate immediate and longer‐term recovery, not only in relation to mental health, but also in relation to behaviour change and adherence, work, education, children and families, physical health and the brain, and social cohesion and connectedness. We call on psychological scientists to work collaboratively with other scientists and stakeholders, establish consortia, and develop innovative research methods while maintaining high‐quality, open, and rigorous research standards.